Analisis Preferensi dan Kepuasan Penerima Bantuan Pangan Non Tunai (BPNT) terhadap Beras di Kota Denpasar - YULANDARI, DEWA AYU INDAH; BUDIASA, I WAYAN; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019DO - 10.24843/JAA.2019.v08.i02.p14, 2019)
Analysis of Preference and Satisfaction of Non-Cash Food Aid Recipients (BPNT) Against Rice in Denpasar City. Income differences are one indicator of differences in social classes. The role of government is very influential in the lower middle class. The government assistance program in the form of Rastra, is channeled in non-cash by transforming from assistance to subsidy patterns to social assistance (food). The purpose of this study to determine the characteristics, preferences and customer satisfaction of rice recipients of Non-Cash Food Aid (BPNT) was assessed from the level of importance and level of performance of the attributes of rice provided by rice suppliers in Denpasar City. Data collection method with survey technique and indepth interview. Data analysis used is descriptive analysis, Customer Satisfaction Index and Importance Performance Analysis. Based on this study the characteristics of the dominating respondents, namely the owner of an electronic account are women as the couple's head of the family. The high and low education does not affect the income they have. Most respondents are from the lower class who are registered as KPM and are entitled to rice assistance from the BPNT program. Rice endurance is the highest value attribute that is an assessment of consumer preferences. The satisfaction index of rice BPNT recipients with a total of 80.46% is in the range of 81% - 100% in the category of very satisfied with some improvements from the results of the IPA method. The results of the Cartesius diagram attribute of rice resistance are the main priority to be improved because it is in quadrant I.